2021
DOI: 10.5187/jast.2021.e53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recovery from short-term heat stress exposure on feed intake, plasma amino acid profiles, and metabolites in growing pigs

Abstract: Effects of recovery from short-term heat stress exposure on feed intake, plasma amino acid profiles, and metabolites in growing pigs Running Title (within 10 words) Effects of heat stress on plasma amino acids and metabolites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(50 reference statements)
0
6
0
1
Order By: Relevance
“…However, it should be noted that the compensatory response was not enough to allow a similar meal size compared to pigs under TN conditions. Although pigs exhibit adaptive FB, the time required for FI recovery after exposure to HS to reach a similar level to that of TN pigs can vary between 2 and 5 days [28,29,30]. However, factors related to the physical capacity of the pigs´ digestive tract and the impact of successive heat waves might not have allowed a full recovery of feed consumption in the current study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, it should be noted that the compensatory response was not enough to allow a similar meal size compared to pigs under TN conditions. Although pigs exhibit adaptive FB, the time required for FI recovery after exposure to HS to reach a similar level to that of TN pigs can vary between 2 and 5 days [28,29,30]. However, factors related to the physical capacity of the pigs´ digestive tract and the impact of successive heat waves might not have allowed a full recovery of feed consumption in the current study.…”
Section: Discussionmentioning
confidence: 83%
“…For feed delivery, the chip in the right ear is identified when each pig introduces its head into the feeder, and when the pig triggers a push button to demand feed, the AIPF delivers a service to each requestion. The service was set to deliver the feed according to the experimental phase (EP), with 20 g during EP1 (0-20 days, 68 to 93 kg of BW) and 23 g during EP2 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) Days 93 to 111 kg of BW). The size of the service was adjusted to be less than 150 services per pig per day following the manufacturer's recommendation.…”
Section: Data Sourcementioning
confidence: 99%
“…However, this hypothesis is currently questioned because other works suggested that HS itself may induce other metabolic alterations caused by intestinal barrier disruption, inflammatory state, postabsorptive metabolism and endocrine responses (Liu et al, 2022; Qaid & Al‐Garadi, 2021). In addition, HS seems to cause oxidative stress and mitochondrial dysfunction by increasing ROS production in muscle cells (Kikusato & Toyomizu, 2013; Kim et al, 2021), whose intracellular signal transduction contributes to protein catabolism. It is noteworthy that pigs with higher genetic potential for lean growth, as well as heavier and older pigs appear to have less tolerance to HS (Renaudeau et al, 2011).…”
Section: Factors Influencing Protein Turnover Ratesmentioning
confidence: 99%
“…Oxidative stress can be viewed as an imbalance between prooxidants and antioxidants in the body [1]. Various stress can adversely affect the structure and physiology of cells, causing impairment of transcription, RNA processing, translation, oxidative metabolism, membrane structure, and function [2,3]. Under normal conditions, A C C E P T E D intracellular levels of reactive oxygen species (ROS) are maintained at low levels by various antioxidant systems [4].…”
Section: Introductionmentioning
confidence: 99%